"Energy supply" and "energy efficiency": specification of concepts, the system of balanced parameters of "energy efficiency"; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Efremov V. V. (Power engineering, 2007)
Заглавие с титульного листа